SOCIO-PHILOSOPHICAL ANALYSIS OF TRENDS IN THE DEVELOPMENT OF VALUES IN THE SYSTEM OF THE GLOBALIZED WORLD (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is devoted to the analysis of the preservation and development of the spiritual values ​​of ethnic groups and peoples in the era of globalization, the reasons for their transformation and disappearance, because values ​​set the historical paths of nations, generate differences and determine the relationships between them.